ChemInform Abstract: Intrinsic Reaction Coordinate: Calculation, Bifurcation, and Automated Search. Issue 4 (January 2016) - Maeda, Satoshi; Harabuchi, Yu; Ono, Yuriko; Taketsugu, Tetsuya; Morokuma, Keiji
Abstract: Review: 173 refs.